1999
DOI: 10.4141/a98-010
|View full text |Cite
|
Sign up to set email alerts
|

Ruminal degradability of alfalfa and corn after processing or maceration

Abstract: . 1999. Ruminal degradability of alfalfa and corn after processing or maceration. Can. J. Anim. Sci. 79: 361-368. The effects of mechanical treatment on ruminal degradability of alfalfa and corn were determined in three experiments using nylon bags incubated in the rumen of two fistulated dry cows. The first experiment was a 2 × 2 × 2 factorial design applied to chopped alfalfa at two levels of mechanical treatment (processing with two corrugated rolls in a forage harvester or no processing), two throughput ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…A potential DM degradability value of approximately 48% was reported by Savoie et al (1999) for chopped LH, which corresponds with the 4 weeks' regrowth value obtained in the current study. The same authors reported a CP degradability value of 57.8%, which is somewhat higher than the values in the current study.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…A potential DM degradability value of approximately 48% was reported by Savoie et al (1999) for chopped LH, which corresponds with the 4 weeks' regrowth value obtained in the current study. The same authors reported a CP degradability value of 57.8%, which is somewhat higher than the values in the current study.…”
Section: Resultssupporting
confidence: 88%
“…In Figure 1, the low rate of NDF degradation of LH harvested after the 6-week regrowth period is evident. A faster rate of protein degradation (c = 0.32) was reported by Savoie et al (1999) which could probably be explained by the fact that the LH was crushed during harvesting in their experiment.…”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations